PEMETAAN POTENSI DEPOSIT ORGANIK DAN BATUAN SEBAGAI BAHAN BAKU PUPUK ALAM DI KABUPATEN KONAWE - Tufaila, Muh.; Alam, Syamsu (Jurnal Agroteknos, 2013)
The research aimed to get nutrients or materials contained in each type of organic deposits and rocks; obtain the type, location and size distribution, and the reserves of organic deposits and rocks that can be used as raw materials for natural fertilizer in to Konawe, and get a map of potential raw materials for natural fertilizer in Konawe. The method used was a survey method followed by chemical analysis of organic deposits and rocks in the laboratory. Data were analysed descriptively. The research results showed that the organic deposits in Konawe were peat and guano deposits. Peat deposits can be used as a source of organic matter while guano deposits as P fertilizer. Peat deposits were located in Lambuya District as many as 2,160,972 tons, while guano deposits were located in Soropia District, Amonggedo, and North Wawonii with the number of deposit of 1,213.16 tons. Rock deposits in Konawe which can be used as raw material for natural fertilizer ultramafic rocks, mica schists and limestones. Ultramafic rocks can be used as Mg fertilizer, mica schist rocks as K fertilizers, and limestones as lime or Ca fertilizer. Deposit ultramafic rocks located in Districts Routa, Lambuya, Pondidaha, West Wawonii, East Wawonii, Middle Wawonii, Southeast Wawonii, North Wawonii, South Wawonii and Northeast Wawonii with the number of deposit of 326.05 million tons. Mica schist rock deposits with located in Districts Routa, Latoma, Asinua, Abuki, Tongauna, Uepai, and Onembute with the number of deposit of 164.16 million tons. Limestone deposit was located in the Districts Routa, Soropia, East Wawonii, Northeast Wawonii and North Wawonii, with the deposit amount 333.04 million tons. Keywords: mapping, natural fertilizer raw materials, organic deposits and rocks